Editorial: Towards 2030: Sustainable Development Goal 8: Decent Work and Economic Growth. A Sociological Perspective - Andrzej Klimczuk; Delali A. Dovie; Minela Kerla; Magdalena Klimczuk-Kochańska; Piotr Toczyski (Frontiers in Sociology, 2024)
This Research Topic explores Sustainable Development Goal (SDG) eight, which is to “promote sustained, inclusive, and sustainable economic growth, full and productive employment, and decent work for all.” It highlights the COVID-19 pandemic's severe impact and triggered global economic recession, worsened gender pay gaps, increased undeclared employment, and significantly raised unemployment (United Nations, 2024). From a sociology-specific perspective, this Research Topic examines the global and local implementation of SDG8, its adaptation to different geographical contexts, stakeholder involvement, and issues related to decent work conditions worldwide.
Keywords: E24; J60; J40; 330; SDG8; unemployment; labor-market issues; social insurance; working poor; precarity; remote work